Relationship between disadaptive personality characteristics and pharmaco-dependency - Macedo-Neuenschwander, Cynthia de (2006)
The purpose of this study was to examine the relation between personality disadaptive characteristics and dependency of psychoactive substances in a sample of pharmacodependent patients. The following instruments were used: Millon´s Multiaxial Clinical Inventory II and Personal Data ficha. Confiability in our milieu was calculated. The non-probabilistic accidental sample consisted of 108 participants, who were dependent on psychoactive substances (alcohol, marihuana, cocaine hydrochloride, freebase cocaine, and other drugs). At the time of this study the participants were being treated in three therapeutic communities and a rehabilitation center for addicts in metropolitan Lima. Results show a high prevalence of disadaptive personality characteristics among participants